Analysis of the School Operational Assistance Funds (Case Study at SMP Negeri 05 Batu) - Thomas Djaka Winarto; Siti Anissah Kiptiyani (University of Merdeka Malang, 2022)
This study aims to determine the realization of the BOS budget and also accountability and transparency of financial reporting at SMP Negeri 05 Batu. The research method used is descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. Sources of data in this study are primary data sources and secondary data. The results show that the implementation of accountability and transparency in the management of BOS funds has been running quite well, namely the existence of RKAS in the planning of BOS funds, compliance with rules and technical instructions for the use and implementation of BOS funds with their realization, as well as the implementation of reporting and accountability of BOS funds to schools, cities/districts and the central government. This fact shows that the school has carried out the BOS fund management process in accordance with government regulations or in the Technical Guidebook.